Statistics for nursing : a practical approach - Heavey, Elizabeth (Burlington, MA : Jone and Bartlett Learning, 2019)
"Statistics for Nursing: A Practical Approach, Third Edition is designed in accordance with the Conversation Theory of Gordon Pask and presents the complicated topic of statistics in an understandable manner for entry level nurses"
Introduction to statistics and levels of measurement -- Presenting data -- Descriptive statistics, probability, and measures of central tendency -- Measuring data -- Sampling methods -- Generating the research idea -- Sample size, effect size, and power -- Chi-square -- Student t-Test -- Analysis of variance (ANOVA) -- Correlation coefficients -- Regression analysis -- Relative risk, odds ratio, and attributable risk.
Includes bibliographical references and index.
Keywords: NURSING -- STATISTICAL METHODS